On the boundedness of the anisotropic fractional maximal operator from anisotropic complementary Morrey-type spaces to anisotropic Morrey-type spaces - Akbulut, Ali; Guliyev, Vagif; Muradova, Sh.A. (Eurasian Mathematical Journal, 2013)
The problem of the boundedness of the anisotropic fractional maximal operator Mdα from anisotropic complementary Morrey-type spaces to anisotropic Morrey-type spaces is reduced to the problem of boundedness of the dual Hardy operator in weighted Lp-spaces on the cone of non-negative non-increasing functions, which allows obtaining sharp sufficient conditions for the boundedness of Mdα.